The March 4, 2021 Kermadec Islands tsunami: records, numerical modeling and warnings in Costa Rica - Porras-Espinoza, Hernán (2022)
On March 4, 2021 a Mw=8.1 earthquake at the Tonga-Kermadec Trench generated a tsunami threat warning from the Pacific Tsunami Warning Center (PTWC).  Costa Rica’s National Tsunami Monitoring System (Sinamot), acting as the National Tsunami Warning Center (NTWC), issued a warning about the possibility of a tsunami. The travel time  of approximately 15 hours allowed the use of tsunami (flooding) numerical modeling as an additional decision support tool. The modeled tsunami heights agreed well with the records from two Costa Rican tide gauges. The tsunami reached a maximum height of 17.6 cm at Quepos (Pez Vela Marina) and 6.1 cm at the Chattam Bay tide gauge at Cocos Island, which was the first tsunami recorded at this gauge since its deployment in March 2018. At Wafer Bay on Cocos Island witnesses filmed the tsunami running upriver and reported strong currents which were not predicted by the model. The contrast between these effects and the small height recorded at the nearby gauge, together with the effects of previous tsunamis, such as the one that occurred in Japan in 2011, confirmed a local effect at Wafer Bay.  For the rest of the country the PTWC forecast overestimated the tsunami heights that were actually recorded, which in turn agreed with the first threat analysis carried out by the Sinamot.